Gestation‐specific D‐dimer reference ranges: a cross‐sectional study. (15th May 2014) - Murphy, N; Broadhurst, DI; Khashan, AS; Gilligan, O; Kenny, LC; O'Donoghue, K
<x xml:space="preserve">Abstract</x> Objective To establish a gestation‐specific reference range for D‐dimer in healthy pregnant women with a singleton pregnancy using the Auto‐Dimer assay. Design Cross‐sectional study Setting Cork University Maternity Hospital, Ireland. Population Healthy pregnant women attending for routine antenatal care. Methods Simultaneous‐quantile regression was performed to construct a median, 5th percentile, and 95th percentile, model of normal pregnancy D‐dimer concentration versus gestational week, ranging from week 6 to 42. Additionally, pair‐wise Mann–Whitney U‐tests were performed to compare distributions of D‐dimer concentrations for each of the four discrete gestational sampling windows with the distribution of D‐dimer concentrations 48 hours postpartum. Main outcome measures D‐dimer concentrations (ng/ml) during normal gestation (approximately week 6 to week 42). Results Seven hundred and sixty healthy pregnant women were investigated between gestational age week 5 and 48 hours postpartum. There was a clear steady increase in median D‐dimer concentrations over the complete gestational period. Additionally, the 95th centile estimates for all gestational time‐points were above the accepted non‐pregnancy normal cut‐off concentration (224 ng/ml). The results of the Mann–Whitney U‐tests suggested that the long‐term postnatal return to normal D‐dimer concentrations begins in the immediate postpartum period. Conclusions We found that there is a continuous increase in D‐dimer concentrations across all gestations. This research is potentially beneficial to future diagnosis of venous thromboembolism (VTE) in pregnancy using the new recommended 95th centile potential cut‐offs. Possible further investigation involves an observational study comparing D‐dimer concentrations in women with proven DVT with those that don't, generating likelihood ratios.